2022
DOI: 10.1093/neuonc/noac042
|View full text |Cite
|
Sign up to set email alerts
|

Distinct metabolic hallmarks of WHO classified adult glioma subtypes

Abstract: Background Gliomas are complex tumors with several genetic aberrations and diverse metabolic programs contributing to their aggressive phenotypes and poor prognoses. This study defines key metabolic features that can be used to differentiate between glioma subtypes, with potential for improved diagnostics and subtype targeted therapy. Methods Cross-platform global metabolomic profiling coupled with clinical, genetic, and path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 62 publications
2
32
2
1
Order By: Relevance
“…Lack of a metabolic signature of IDH-mutant gliomas beyond elevated 2-HG in our data could be due to a smaller cohort of patients lacking in low-grade astrocytomas. Indeed the clustering of grade 4 IDH-mutant astrocytomas with lower grade IDH-mutant gliomas in tissue metabolomic analyses was solely dependent on 2-HG 36 . Future studies will be needed to directly compare the extracellular versus tissue metabolome in paired patient samples.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lack of a metabolic signature of IDH-mutant gliomas beyond elevated 2-HG in our data could be due to a smaller cohort of patients lacking in low-grade astrocytomas. Indeed the clustering of grade 4 IDH-mutant astrocytomas with lower grade IDH-mutant gliomas in tissue metabolomic analyses was solely dependent on 2-HG 36 . Future studies will be needed to directly compare the extracellular versus tissue metabolome in paired patient samples.…”
Section: Discussionmentioning
confidence: 96%
“…S4B) . Recently published work from over 200 glioma tissues demonstrated significant metabolic heterogeneity in IDH-mutant gliomas and separation of IDH-mutant from IDH-WT tumors, albeit with fewer metabolites differentiating IDH-mutant grade 4 astrocytomas from GBMs 36 . Lack of a metabolic signature of IDH-mutant gliomas beyond elevated 2-HG in our data could be due to a smaller cohort of patients lacking in low-grade astrocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with previous. Meanwhile, we analyzed the expression of FDX1 protein in glioma cells by HPA (Human Protein Database) 8 . The results showed that FDX1 protein was expressed in the glioma cell line U251 cells, and was mainly expressed in the cytoplasm and cell membrane (Figure 2C).…”
Section: Abnormally Expression Of Fdx1 Gene In Gliomasmentioning
confidence: 99%
“…Glioma is one of the most common central nervous system malignancies (1)(2)(3)(4)(5)(6). Evidence shows that high-grade glioma (HGG) has obvious aggressiveness and heterogeneity (7)(8)(9)(10)(11)(12)(13)(14). In 2022, the World Health Organization (WHO) updated the classification criteria of glioma according to the molecular characteristics of different gliomas, which will help patients obtain more accurate diagnoses and precise personalized treatment in clinical practice (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, after analyzing 224 different grades of glioma tissues, Bjorkblom et al found higher levels of glycine and 2-aminoadipic acid in IDH mutated higher-grade gliomas. In low-grade astrocytoma and oligodendroglioma, elevated N-acetyl aspartic acid was closely related to IDH mutations [ 103 ]. In the cerebrospinal fluid from patients with IDH mutated gliomas, alanine was usually decreased [ 104 ].…”
Section: Idh Mutations and Aa Metabolic Alterationmentioning
confidence: 99%